2005
DOI: 10.1084/jem.20051100
|View full text |Cite
|
Sign up to set email alerts
|

Functional specialization of gut CD103+ dendritic cells in the regulation of tissue-selective T cell homing

Abstract: Gut-associated lymphoid tissue (GALT) dendritic cells (DCs) display a unique ability to generate CCR9+ α 4 β 7 + gut-tropic CD8+ effector T cells. We demonstrate efficient induction of CCR9 and α 4 β 7 on CD8+ T cells in mesenteric lymph nodes (MLNs) after oral but not intraperitoneal (i.p.) antigen administration indicating differential targeting of DCs via the oral route. In vitro, lamina propria (LP)–derived DCs were more potent than MLN or Peyer's patch DCs in their ability to generate CCR9+ α 4 β 7 + CD8+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
612
2
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 628 publications
(660 citation statements)
references
References 41 publications
40
612
2
6
Order By: Relevance
“…25 Our results showing that Hic1 DT mice had reduced numbers of intestinal T cells could be owing to reduced expression of intestinal homing molecules, resulting in impaired intestinal migration. However, we failed to observe any reduction in expression of a4b7 and CCR9 on T H cells in the presence or absence of HIC1 following activation in the presence of RA (Figure 5a).…”
Section: Hic1 Is Dispensable For Expression Of Intestinal Homing Recementioning
confidence: 77%
See 1 more Smart Citation
“…25 Our results showing that Hic1 DT mice had reduced numbers of intestinal T cells could be owing to reduced expression of intestinal homing molecules, resulting in impaired intestinal migration. However, we failed to observe any reduction in expression of a4b7 and CCR9 on T H cells in the presence or absence of HIC1 following activation in the presence of RA (Figure 5a).…”
Section: Hic1 Is Dispensable For Expression Of Intestinal Homing Recementioning
confidence: 77%
“…22 Previous studies have shown that mice raised on a diet lacking vitamin A (VAD diet) have defects in T H -cell activation and intestinal migration, resulting in an overall impairment in T-cell-driven immune responses in the intestine. [23][24][25] To test whether RA influenced HIC1 expression in intestinal T H cells, we raised Hic1 Citrine mice on a VAD diet. We found that LP T H cells from VAD mice failed to express HIC1 (Figure 4a), suggesting that HIC1 expression in T H cells in the LP is dependent on the presence of RA.…”
Section: Ra Regulates Expression Of Hic1 In T Cells In Vitro and In Vivomentioning
confidence: 99%
“…We and others [6][7][8][9] have identified and characterised a specialised population of MLN DC that express the integrin a E chain, CD103. CD103 1 DC represent a sentinel DC population in the small intestine (SI) and can migrate to the MLN to initiate adaptive immune responses [10].…”
Section: Introductionmentioning
confidence: 96%
“…One possibility is that these activities are mediated by distinct DC populations and indeed many subtypes of DC have been identified in the gut [4]. It has been proposed that resident gutconditioned DC may favour tolerogenic responses, whereas newly recruited inflammatory DC may drive host protective immunity.Alternatively, tissue-resident DC may adopt distinct functions under homeostatic and inflammatory conditions [4,5].We and others [6][7][8][9] have identified and characterised a specialised population of MLN DC that express the integrin a E chain, CD103. CD103 1 DC represent a sentinel DC population in the small intestine (SI) and can migrate to the MLN to initiate adaptive immune responses [10].…”
mentioning
confidence: 97%
“…For example, T cells activated in mLN and PP draining the gut acquire high levels of the integrin a 4 b 7 , whereas activation in skin-draining peripheral LN (pLN) results in the upregulation of selectin ligands such as P-lig. Tissuespecific DC have been shown in a number of in vitro and in vivo studies to be involved in the instruction of naïve T cells [4,[17][18][19][20][22][23][24] reported that GALT DC were capable of converting metabolites of dietary vitamin A into retinoic acid (RA), which in turn induced T cell expression of a 4 b 7 and CCR9, leading to the generation of gut-tropic T cells. However, the factors, which are involved in the generation of skin-specific T cell homing in vivo, are largely unknown, although important roles for cytokines including IL-12 and TGF-b have been suggested from in vitro studies [26][27][28].…”
Section: Introductionmentioning
confidence: 99%